Transcatheter Aortic Valve Durability: Focus on Structural Valve Deterioration - Antonin Trimaille; Adrien Carmona; Sandy Hmadeh; Dinh Phi Truong; Benjamin Marchandot; Shinnosuke Kikuchi; Kensuke Matsushita; Patrick Ohlmann; Valérie Schini‐Kerth; Josep Rodés‐Cabau; Philippe Pibarot; Olivier Morel (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Transcatheter aortic valve replacement has emerged as a valuable alternative to surgical aortic valve replacement in patients with severe aortic stenosis. Given the expansion of transcatheter aortic valve replacement to lower‐risk and younger populations with longer life expectancy, the durability of transcatheter heart valves (THVs) has become an important issue that may impact cardiovascular outcomes. THVs share similarities with surgical valves but have unique features, including a trend to larger effective orifice area and less prosthesis–patient mismatch, interactions with the native valve, and crimping process, that may all potentially influence a THV's life span. Multiple mechanisms may lead to bioprosthetic valve dysfunction, including structural valve deterioration, thrombosis, endocarditis, and nonstructural valve deterioration. With an incidence of up to 12.3% 5 years after transcatheter aortic valve replacement, structural valve deterioration represents the ultimate consequence of fibrotic remodeling and calcification within the bioprosthesis, driven by thrombotic and inflammatory processes involving the native aortic valve and influenced by patient and procedural factors. Understanding these mechanisms is crucial for improving THV durability.